Effects of shading on herbaceous plant patches transplanted reciprocally between three shading treatments - Kyriazopoulos A.P.; Nastis A.S. (Nutritional and foraging ecology of sheep and goats, 2009)
The effect of three shading origins and of three shading levels on the above-ground production and nutritive value of herbaceous vegetation were studied for two years. The experiment was conducted in Laggadia, north of the city of Thessaloniki, Greece close to the borders of the FYROM. Three treatments, 0% shading level (open grassland), 75% shading level (medium density forested area) and 95% shading level (high density forested area) were studied. From each origin 45 patches 30 × 30 cm were dug and then transplanted,15 patches to each treatment. The experimental layout was a split plot design. It included the three shading origins as the whole pots and the three shading treatments as sub-plots. Herbage production, CP and ADF contents were not affected by the shading origin, while NDF content was higher and ADL lower for the patches originating from the open area. Average herbage production and ADF content were statistically different between shading levels: they were higher for the open area compared to medium and high density forest stands. Only high shading resulted in significantly higher CP values on average, while NDF and ADL content was not affected by shading levels.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)